A Botucatu dos sonhos dos idosos - Inoue, Satiko Aoki (2007)
The major objective of this research project is to investigate in depth the meaning of aging and the self-perception of being elderly. Furthermore, it aims to investigate what elderly people s lives, wishes and dreams are like in Botucatu city, Brazil. Based on interviews carried out with local elderly people, this study also aims to eventually help improve how this very population is looked after by Botucatu s society and institutions. Local elderly-oriented organizations with individual social care projects and Christian Pastoral Ecclesiastic groups have been studied. Semistructured interviews have been conducted and were based on an extensive list of questions designed earlier from a thorough literature review. Results revealed a unique self-perception of being elderly and facing aging. The elderly wish there were new public policies from which they could benefit from. Even though Botucatu does not offer efficient elderly-related social care services, most of the elderly in the city face aging in a positive and happy way. From this standpoint, such happiness turns Botucatu into a potentially suitable city to live in and fulfill the elderly s dreams and wishes